2017
DOI: 10.4300/jgme-d-17-00952.1
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Context: Exploring Aims, Improvement Priorities, and Environmental Considerations in a National Sample of Programs Using “Small Data”

Abstract: Background In 2013, the Accreditation Council for Graduate Medical Education (ACGME) transitioned into a new accreditation system to reduce burden, focus on outcomes, and promote innovation and improvement. One component is a self-study that includes aims, an environmental assessment, and setting improvement priorities. The ACGME initiated voluntary site visits following the self-study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Reports from residents gleaned from open-ended interviews during experimental nonaccreditation site visits suggest both appropriate variance in supervision to match trainee levels and variance among individual attending physicians, with some offering more and some providing less supervision for a given level of resident competence. 23 Residents expressed concerns about undersupervision and uncertainty early in training, but had concerns about oversupervision as they neared completion of their training and began the transition to practice. 23 Working without adequate supervision is among a set of variables that interact in the intricate process of residency training and the process of becoming a professional.…”
Section: Discussionmentioning
confidence: 99%
“…Reports from residents gleaned from open-ended interviews during experimental nonaccreditation site visits suggest both appropriate variance in supervision to match trainee levels and variance among individual attending physicians, with some offering more and some providing less supervision for a given level of resident competence. 23 Residents expressed concerns about undersupervision and uncertainty early in training, but had concerns about oversupervision as they neared completion of their training and began the transition to practice. 23 Working without adequate supervision is among a set of variables that interact in the intricate process of residency training and the process of becoming a professional.…”
Section: Discussionmentioning
confidence: 99%
“…One study that examined common themes in aims and environmental factors from close to 400 different programs found several common themes from programs spanning different specialties and institutions. 11 It is important to note also that the NAS places greater responsibility on the core program for oversight of the dependent subspecialty programs, 10 and active involvement of the core program in fellowship self-studies is therefore important from a regulatory perspective as well.…”
Section: Core and Subspecialty Programs Working Togethermentioning
confidence: 99%
“…Aims often relate to the attributes of graduates, and in an earlier article, we identified that educating physicians to be fully prepared for unsupervised practice is a common aim across a range of specialties. 3 Other aims for graduates may emphasize future careers in academic medicine, research and generating new knowledge, or practice in underserved areas. A less frequently seen, yet highly useful set of aims relates to the attributes of the program itself, such as providing ''a culture that is supportive, respectful, and compassionate toward trainees, patients, and colleagues.''…”
Section: Linking Improvement To Aims and Contextmentioning
confidence: 99%
“…At the same time, findings from programs that underwent a voluntary pilot visit suggest that, not infrequently, there is conflict between program and departmental or institutional priorities, such as the program's aim to educate generalist physicians conflicting with its department's efforts to increase subspecialty faculty and a focus on subspecialized care. 3 This suggests a need for conversations with department and institutional leadership, when program aims and department and institutional goals appear to be in conflict, to ensure appropriate support for important program aims.…”
Section: Coordination Between Program Departmental and Institutionamentioning
confidence: 99%
See 1 more Smart Citation